Development of the core outcome set for herbal medicine treatment of lumbar disc herniation (COS-HM-LDH): A study protocol for a systematic review and a delphi survey - Soo-Dam Kim; Changsop Yang; Mi Mi Ko; Kyung-Min Shin; Sungha Kim; Myeong Soo Lee (PLoS ONE, 2025)
Background Lumbar Disc Herniation (LDH) is a common global musculoskeletal disorder that causes a significant socioeconomic burden. Nonsurgical interventions are the primary treatment; however, herbal medicines (HM) are gaining traction for their efficacy in managing LDH. Conversely, their integration into clinical settings is limited owing to inconsistencies in clinical trial methodologies, mainly stemming from a lack of standardized outcome measures. Our research, highlighting this gap, sought to develop a Core Outcome Set (COS) to consistently assess HM treatments for LDH in Korean medicine (KM) clinical institutions using a consensus-driven, multi-phased approach. Methods The development of the COS-HM-LDH involves four main phases: (1) a project management group (PMG) conducts a systematic review to curate an initial list of outcomes; (2) several Delphi survey rounds are administered to a selected panel of experts to validate and refine these outcomes; (3) KM clinicians are involved in a subsequent Delphi survey to further refine the outcomes; and (4) a final consensus meeting finalizes the COS. Discussion The lack of a standardized COS for HM treatment of LDH in KM introduces biases and discrepancies in clinical practice. The proposed COS aims to provide a unified framework, given the challenges faced in clinical trials, especially in KM institutions. This initiative is expected to strengthen evidence quality, foster greater trust, and facilitate wider clinical implementation of HM treatment for LDH. Trial registration The Core Outcome Measures in Effectiveness Trials (COMET) Initiative: https://www.comet-initiative.org/Studies/Details/2909